2017
DOI: 10.1155/2017/1650194
|View full text |Cite
|
Sign up to set email alerts
|

Use of Nonvascularized Autologous Fibular Strut Graft in the Treatment of Major Bone Defect after Periprosthetic Knee Fracture

Abstract: We present the case of a patient who suffered a comminuted supracondylar periprosthetic femur fracture. The patient was an 86-year-old lady who suffered a minor fall at home and presented at our hospital with a right comminuted distal femur fracture around a total knee arthroplasty. The patient was submitted to a cruciate-sacrificing total knee replacement 6 years before at the same institution. Despite severe metaphyseal fragmentation and short distal fragment, the prosthesis was stable; thus, open fracture r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…El resultado final del uso de aloinjertos en el manejo de defectos óseos segmentarios está directamente relacionado con la técnica quirúrgica empleada en la toma del injerto y con la posterior aplicación de este en sitios con adecuada cobertura y vascularización. Se ha establecido que los injertos vascularizados requieren mayor tiempo para lograr una integración y su evolución satisfactoria dependerán fundamentalmente de los tejidos de cubrimiento 6,9 .…”
Section: Discussionunclassified
“…El resultado final del uso de aloinjertos en el manejo de defectos óseos segmentarios está directamente relacionado con la técnica quirúrgica empleada en la toma del injerto y con la posterior aplicación de este en sitios con adecuada cobertura y vascularización. Se ha establecido que los injertos vascularizados requieren mayor tiempo para lograr una integración y su evolución satisfactoria dependerán fundamentalmente de los tejidos de cubrimiento 6,9 .…”
Section: Discussionunclassified
“…The titanium plate was removed (e) et al [16] had successfully repaired one ankle joint with a 15-cm non-vascularized fibular flap. Moreover, Giordano et al [19] also adopted a 21-cm non-vascular fibular flap to successfully repair the distal femoral condyle defect in an 86-year-old patient. All these successful cases mentioned above have indicated that it is feasible to reconstruct bone defects with the non-vascular fibula in clinical practice [20].…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al (10) successfully repaired one ankle joint with a 15 cm NVFF. Giordano et al (13) harvested a 21 cm of NVFF and divided it into 9 cm and 12 cm approximately, which were then used to successfully repair the distal femoral condyle defect in a 86-year-old patient caused by a comminuted fracture of the distal femur. Compared with vascularized fibular graft, NVFF is associated with a certain risk of failure, but the above-mentioned successful cases also indicate that, it is feasible to the reconstruct bone defects using NVFF in the clinic (14).…”
Section: Discussionmentioning
confidence: 99%